A field full of green stars: Paepalanthus multistellaris (Eriocaulaceae), a new species from Minas Gerais, Brazil - Andrino, Caroline Oliveira; Trovó, Marcelo; Sano, Paulo Takeo (Phytotaxa, 2016)
We describe and illustrate Paepalanthus multistellaris, a remarkable new species of Eriocaulaceae from the northern Espinhaço Range in Minas Gerais, Brazil. The species is known from a single population growing between the campos rupestres and veredas in the municipality of Botumirim. This new species is placed into P. subsect. Actinocephaloides, and is characterized by its long, ascending stem, scapes arranged in a fasciculate, umbel-shaped inflorescence, and green involucral bracts surpassing the flowers. Illustrations, photos, and a detailed description, as well as comments on habitat, morphology, and affinities with similar species are provided. The species is considered Critically Endangered, according to the IUCN Red List categories and criteria.